2013
DOI: 10.1007/s12017-013-8223-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Specific Expression of Tomosyn1 in the Mouse Hippocampal Dentate Gyrus Impairs Spatial Learning and Memory

Abstract: Tomosyn, a syntaxin-binding protein, is known to inhibit vesicle priming and synaptic transmission via interference with the formation of SNARE complexes. Using a lentiviral vector, we specifically overexpressed tomosyn1 in hippocampal dentate gyrus neurons in adult mice. Mice were then subjected to spatial learning and memory tasks and electrophysiological measurements from hippocampal slices. Tomosyn1-overexpression significantly impaired hippocampus-dependent spatial memory while tested in the Morris water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…We found that EE increases the level of the presynaptic protein synaptophysin that is positively involved in synaptic transmission, and decreases the level of tomosyn, a protein that inhibits synaptic transmission. The fact that synaptophysin is associated with the efficacy of synaptic transmission, 79 and that tomosyn is a negative regulator of the neurotransmission process, 62, 63, 64, 65, 66, 67, 68, 69, 103 together with our findings, add to our understanding of how exposure to EE may improve neurotransmission. In contrast, in old and very old 3xTgAD mice, tomosyn levels in the hippocampus were significantly higher compared with young 3xTgAD mice.…”
Section: Discussionsupporting
confidence: 63%
“…We found that EE increases the level of the presynaptic protein synaptophysin that is positively involved in synaptic transmission, and decreases the level of tomosyn, a protein that inhibits synaptic transmission. The fact that synaptophysin is associated with the efficacy of synaptic transmission, 79 and that tomosyn is a negative regulator of the neurotransmission process, 62, 63, 64, 65, 66, 67, 68, 69, 103 together with our findings, add to our understanding of how exposure to EE may improve neurotransmission. In contrast, in old and very old 3xTgAD mice, tomosyn levels in the hippocampus were significantly higher compared with young 3xTgAD mice.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown that tomosyn over-expression reduces synaptic transmission at various synapses (Barak et al, 2013a; Hu et al, 2013) however, the effects of tomosyn KO and KD have produced conflicting results (Baba et al, 2005; Cheviet et al, 2006; Gracheva et al, 2007; McEwen et al, 2006; Sakisaka et al, 2008; Zhang et al, 2006). Consistent with the high expression levels of tomosyn in MFs (Barak et al, 2010; Sakisaka et al, 2008), our findings showing a robust reduction in the magnitude of STP at tomosyn-deficient MF-CA3 synapses, strongly suggest that tomosyn is an important negative regulator of P r at this synapse.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent discrepancy could be due to compensatory changes likely occurring in KO mice. Another study showed that tomosyn over-expression via lentiviral transduction of DGCs did not alter MF-LTP or LFF (Barak et al, 2013a). However, as seen in our new study, electrical stimulation is sub-optimal when compared to optical stimulation and could have underestimated the actual effect of tomosyn on MF-CA3 synaptic function.…”
Section: Discussionmentioning
confidence: 99%
“…STXBP5 encodes a syntaxin-binding protein, tomosyn that negatively regulates neurotransmitter release by forming a syntaxin-SNAP25-tomosyn complex (Fujita et al, 1998; Sakisaka et al, 2004; Yizhar et al, 2004; Yamamoto et al, 2009, 2010; Bielopolski et al, 2014). Neuron-specific tomosyn deletion in mouse hippocampal dentate gyrus impairs spatial learning and memory, whereas tomosyn knockdown in dentate gyrus decreases synaptic plasticity of mossy fibers (Barak et al, 2013; Ben-Simon et al, 2015). Tomosyn also regulates SNARE complexes via ROCK phosphorylation of syntaxin-1 to control neurite outgrowth (Sakisaka et al, 2004).…”
Section: Synaptic Proteins Regulate Synaptic Function To Maintain Neumentioning
confidence: 99%